The Impact of the QRIS Payment System on the Digital Economy Development - Utami, Budi (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2024)
The digital economy continues to experience rapid development in Indonesia, especially in the fields of e-commerce and financial technology. Cashless payments are increasingly becoming a trend among Indonesians both in urban and rural areas. The use of the QR Code Indonesian Standard (QRIS) payment method began to be used as a merchant transaction tool. Since November 1, 2021, the number of QRIS merchants has exceeded 12 million. The use of QRIS is an opportunity in the development of the digital economy. This research is a literature study research that is analyzed using a qualitative-descriptive approach in explaining phenomena related to QRIS implementation of the digital economy. The data sources used are secondary data sources derived from books, journals, and reports related to economic digitization. The results of the study found that QRIS has a positive influence on the development of the digital economy in Indonesia. This is marked by the increase in Indonesia's Gross Merchandise Value (GMV). The comprehensive use of QRIS can also help the country in controlling the inflation rate to be low and stable because it reduces cash printing activities and transactions to be transparent with a structured system.